Researchers put UMP Flag in USA - UMP, PNC
Dr. Arun Gupta, Senior Lecturer from Faculty of Chemical & Natural Resources Engineering (FKKSA), received gold medal for his project on “Nano-wood composite” in Furniture Category at The Invention & New Product Exposition (INPEX) 2011 at Pittsburgh, USA recently.